DAMPAK PENUTUPAN AKUN TIK-TOK SHOP: ANCAMAN DAN PELUANG USAHA MIKRO KECIL MENENGAH (UMKM)? - Fitriya, Elok; Sumowo, Seno (Universitas Muhammadiyah Jember, 2024)
Abstract: The Indonesian government has expressed its concerns about the negative impact of TikTok Shop on local MSMEs. They think that TikTok Shop could be a way for companies to collect data on products that are selling well in a country, then produce similar goods abroad at cheaper prices. Thus, TikTok Shop not only threatens the existence of local MSMEs, but also the economic sovereignty of a country. Seeing these impacts, there is a strong argument for separating social media platforms and e-commerce platforms like TikTok Shop. While the separation between social media platforms and e-commerce platforms has clear benefits, there are also challenges. One of the main challenges is how to implement this separation without disrupting the user experience. TikTok has become a very popular platform with many users accustomed to the integration of social media and e-commerce. Separating the two may require significant technical adjustments and development. In an era where social media and e-commerce are increasingly integrated, the debate about the separation between the two becomes increasingly relevant. TikTok Shop, as a recent example, has raised questions about appropriate policies to protect local MSMEs and consumers.Key word: Tik-tock shop, threats, opportunities Abstrak: Pemerintah Indonesia telah menyampaikan keprihatinannya tentang dampak negatif TikTok Shop pada UMKM lokal. Mereka menilai bahwa TikTok Shop bisa menjadi cara bagi perusahaan untuk mengumpulkan data produk yang laris-manis di suatu negara, lalu memproduksi barang serupa di luar negeri dengan harga lebih murah. Dengan demikian, TikTok Shop tidak hanya mengancam eksistensi UMKM lokal, tetapi juga kedaulatan ekonomi suatu negara. Melihat dampak-dampak tersebut, ada argumen yang kuat untuk memisahkan platform media sosial dan platform e-commerce seperti TikTok Shop. Meskipun pemisahan antara platform media sosial dan platform e-commerce memiliki manfaat yang jelas, juga ada tantangan. Salah satu tantangan utama adalah bagaimana mengimplementasikan pemisahan ini tanpa mengganggu pengalaman pengguna. TikTok telah menjadi platform yang sangat populer dengan banyak pengguna yang terbiasa dengan integrasi media sosial dan e-commerce. Memisahkan keduanya mungkin memerlukan penyesuaian dan pengembangan teknis yang signifikan. Dalam era di mana media sosial dan e-commerce semakin terintegrasi, perdebatan tentang pemisahan antara keduanya menjadi semakin relevan. TikTok Shop, sebagai contoh terkini, telah memunculkan pertanyaan tentang kebijakan yang tepat untuk melindungi UMKM lokal dan konsumen.Kata Kunci : Tik-tok shop, ancaman, peluang